A review of emerging factor XI inhibitors. (2nd January 2023) - Elsheikh, Sandra; Tidbury, Nicola; Lip, Gregory Y.H.
ABSTRACT: Introduction: Whilst the introduction of direct oral anticoagulants (DOACs) has improved the prevention of thromboembolic events, there is still a need for safer anticoagulants. This is particularly so, for specific populations of patients, such as those with an increased bleeding risk or those with severely reduced kidney function. People with Factor XI (FXI) deficiency are at reduced risk of thromboembolic events, without an increased risk of spontaneous bleeding. FXI inhibition, therefore, presents the ideal target for novel anticoagulants. Areas covered: In this review, we provide an overview of the currently available anticoagulants and the emerging FXIa inhibitors in clinical trials. The need for availability of novel anticoagulants and the potential issues that will hinder the development and marketing of factor XIa inhibitors is also discussed. Expert opinion: Evidence suggests that FXI inhibition presents a promising drug target for novel anticoagulation therapies. The FXIa inhibitors in development have advantages over DOACs with lower renal clearance and long half-lives. Overall, FXI inhibition presents a promising target, it is likely that the clinical use of FXIa inhibitors is on the horizon.